Workability and Flexural Strength of Recycled Aggregate Concrete with Steel Fibers - Chachar, Kashif Hassan; Oad, Mahboob; Memon, Bashir Ahmed; Siyal, Zameer Ahmed; Siyal, Kiran Fatima (Engineering, Technology & Applied Science Research, 2023)
This study examined how concrete workability and flexural strength are affected by steel fibers and recycled aggregates. Steel fibers were used in doses between 1-5%, with an increment of 0.5%, and 50% of the natural coarse aggregates were replaced by recycled. Two mixes of conventional and recycled aggregate concrete without steel fibers were used as control mixes. Concrete mixes were prepared using 1:2:4 and 0.45 water-to-cement ratios. Workability was determined using the slump cone. Three prism specimens sized 500×100×100mm were prepared for each batch and cured for 28 days in potable water. After curing, the specimens were air-dried in the laboratory and tested to evaluate their flexural strength under two-point loading. The load and deflection were monitored at regular intervals until failure. A comparison of results with control mixes showed that as the percentage of steel fiber increased, flexural strength increased by 69% and deflection decreased by 66%. The use of steel fibers improved the flexural strength of the recycled aggregate concrete by 59%.